Achieving increased bandwidth for 4 degree of freedom self-tuning energy harvester. (28th April 2018) - Staaf, L.G.H.; Smith, A.D.; Köhler, E.; Lundgren, P.; Folkow, P.D.; Enoksson, P.
Abstract: The frequency response of a self-tuning energy harvester composed of two piezoelectric cantilevers connected by a middle beam with a sliding mass is investigated. Measurements show that incorporation of a free-sliding mass increases the bandwidth. Using an analytical model, the system is explained through close investigation of the resonance modes. Resonance mode behavior further suggests that, by breaking the symmetry of the system, even broader bandwidths are achievable.